Desenvolvimento de indicadores de eficiência energética para avaliação de pivôs centrais de irrigação - Lima, Aureo Cezar de (2008)
The task of this work is to present the development of some indicators and to create a label and energy efficiency standards for central pivoting irrigation systems. Firstly were presented policies and programs related to the efficient use of electrical energy and the methodology for the evaluation of such systems. With the approach of efficiency, losses in suction subsystems, electrical motors and pumps, pipes, lateral lines and aspersion are determined, with the application of indices available in the literature and proposed in this work. The development of indices were made to integrate energy and hydraulic parameters in central pivoting irrigation systems in order to clearly characterize them, as an aid to the user and buyer, and to stimulate the competition among different central pivoting assembling companies. Such indices are applied in four central pivoting irrigation systems, one at EMPBRAPA Agropecuaria Oeste and three at Assentamento Itamarati 1, where irrigation efficiencies between 8.9% and 21.8% were obtained. Through economic analysis, new projects show irrigation efficiency indices above 23.4% and a standard called Irrigation Normalized Specific Consumption equal to 8.68 kWh/(mm.ha.100m). The expected benefit due to the energy efficiency measures can reach 260.2 thousand Reais/year in Assentamento Itamarati 1 systems, extrapolating to the national use of central pivoting, which allows an economy of 229.4 GWh/year, or else, to avoid 40.72 million of Reais/year spent in electrical energy in such irrigation systems in the country.